2022
DOI: 10.1158/0008-5472.can-21-3748
|View full text |Cite
|
Sign up to set email alerts
|

RNA Helicase DDX24 Stabilizes LAMB1 to Promote Hepatocellular Carcinoma Progression

Abstract: Hepatocellular carcinoma (HCC) is one of the most aggressive malignancies. Elucidating the underlying mechanisms of this disease could provide new therapeutic strategies for treating HCC. Here, we identified a novel role of DEAD-box helicase 24 (DDX24), a member of the DEAD-box protein family, in promoting HCC progression. DDX24 levels were significantly elevated in HCC tissues and were associated with poor prognosis of HCC. Overexpression of DDX24 promoted HCC migration and proliferation in vitro and in vivo,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…To identify the region of binding on FANCA mRNA, we used the RSAT (Regulatory Sequence Analysis Tools) website tool (http://rsat.sb-roscoff.fr/matrix-scan.cgi) to scan FANCA mRNA sequence with the motif we reported previously. 29 We identified 6 putative binding sites and constructed 5 corresponding probes for RNA pull-down assay (Figure 5F). The results revealed that the region 1721 to 2845 nucleotide (including site 3) in FANCA mRNA was critical for DDX24 binding (Figure 5G).…”
Section: Resultsmentioning
confidence: 99%
“…To identify the region of binding on FANCA mRNA, we used the RSAT (Regulatory Sequence Analysis Tools) website tool (http://rsat.sb-roscoff.fr/matrix-scan.cgi) to scan FANCA mRNA sequence with the motif we reported previously. 29 We identified 6 putative binding sites and constructed 5 corresponding probes for RNA pull-down assay (Figure 5F). The results revealed that the region 1721 to 2845 nucleotide (including site 3) in FANCA mRNA was critical for DDX24 binding (Figure 5G).…”
Section: Resultsmentioning
confidence: 99%
“…It is known that among the DEAD-box RNA helicases, DDX6 is involved in a wide range of RNA life processes: translation inhibition, mRNA degradation, transport and storage, translation activation, and nuclear export [ 45 ]. For DDX24, a correlation has been shown between its elevated levels in hepatocellular carcinoma tissues and poor prognosis of this disease [ 47 ]. Interestingly, DDX24 is necessary for the organization of muscle fibers and specification of the anterior pole, which is important for regenerating the head in planarians [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…In HCC, ADAM9 is known to be overexpressed and is responsible for inducing ROS generation, which in turn promotes HCC cell invasion ( 34 ). Additionally, LAMB1 has been shown to be regulated by the RNA helicase DDX24, which contributes to the malignant progression of HCC ( 35 ). However, the role of SPON2 in HCC is still a matter of debate.…”
Section: Discussionmentioning
confidence: 99%